Shear acoustic waves in plates - KIEŁCZYŃSKI, P.; PAJEWSKI, W.; SZALEWSKI, M. (Archives of Acoustics, 1992)
In the paper the theoretical analysis and results of experimental investigations of SH waves propagation in plates are presented. The dimensions of different plates and methods of SH wave excitation were applied in order to attain mode separation and identification.